A rare case of peritoneo-cutaneous fistula after laparoscopy converted to open failed cholecystectomy: meticulously managed by laparoscopy - Khan, Washim F.; Rathore, Yashwant S.; Singh, Gurpremjit; Jain, Sandeep; Singh, Devender (International Surgery Journal, 2019)
Peritoneo-cutaneous fistula can occur following cholecystectomy due to leftover stones. However, cholecysto-cutaneous fistula has been found to be associated with complication of acute cholecystitis. But never before a fistula associated with abandoned cholecystectomy without spillage of stone have been described in literature. We describe a case report of a 25-year-old female presented with right upper quadrant serous discharge from a previous incision site for the past 8 months. The patient had a history of failed cholecystectomy one year back. The patient was evaluated radiologically with computed tomography sinogram and magnetic resonance cholangiopancreatogram (MRCP) and found to have a tract communicating with subcutaneous tissue and gallbladder fossa with normal gallbladder anatomy and a single calculus. The patient was managed laparoscopically. Laparoscopic cholecystectomy was performed successfully with excision of peritoneo-cutaneous fistula tract. All difficult and failed cholecystectomies should be attempted at high volume surgical centres by an experienced laparoscopic surgeon only.